2017
DOI: 10.14310/horm.2002.1742
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and obesity: implications for fecal microbiota transplantation therapy

Abstract: Obesity is a major public health issue as it is causally associated with several chronic disorders, including type-2 diabetes, cerebrovascular disease (CVD), and cancer. In the United States and other countries worldwide, the obesity epidemic has drastically impacted the status of health of millions as well as healthcare costs. Aside from poor diet, hygiene, and genetics, there are many other factors thought to play an important role in the emergence of obesity. Nowadays, accumulating evidence is elucidating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…In fact, obesity itself, with or without a high fat-diet intake, can shape the gut microbiota. On the other hand, this “obese” microbiota can reprogram the gut as well as the entire body to maximize nutrient absorption and an accumulative metabolism [ 74 ]. Furthermore, this shift in microbial populations has been associated with a metabolic endotoxaemia due to higher LPS passage through an impaired IP [ 75 ].…”
Section: Gut Microbiota Immune System and Liver Diseasesmentioning
confidence: 99%
“…In fact, obesity itself, with or without a high fat-diet intake, can shape the gut microbiota. On the other hand, this “obese” microbiota can reprogram the gut as well as the entire body to maximize nutrient absorption and an accumulative metabolism [ 74 ]. Furthermore, this shift in microbial populations has been associated with a metabolic endotoxaemia due to higher LPS passage through an impaired IP [ 75 ].…”
Section: Gut Microbiota Immune System and Liver Diseasesmentioning
confidence: 99%
“…Compared with classical statistical methods, machine learning is more suitable for dealing with large-scale learning problems and shows excellent performance when dealing with high-dimensional structured data obtained by metagenomic sequencing [ 7 ]. Machine learning methods can deeply mine the interaction information contained in the flora data by extracting features, which can deal with a variety of biological information problems, identify relevant biomarker variables based on sparse data, and prevent overfitting [ 8 ]. For multitask problems, the performance is improved by using information from various related tasks, for clustering feature analysis of unlabeled data [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The oral cavity is an important location of intestinal microbiota, which has an important effect on human health. Studies have shown that children who grow up on farms have a lower risk of asthma; a phenomenon that may be linked to changes in their gut microbiota[ 8 ]. In addition, babies born by cesarean section are at increased risk of developing autoimmune diseases, mainly because the initial microbes passed from the vagina to the baby at birth are replaced by skin microbes from the mother and surgical team members, which alter the baby’s gut microbes[ 9 ].…”
Section: Composition and Methods Of Fmtmentioning
confidence: 99%